Effect of High Temperature on the Mechanical Performance of Additively Manufactured CoCrNi Medium-Entropy Alloy Octet-Truss Lattice Materials - Zhijia Zhang; Bowen Yang; Yongjing Wang; Jun Ma; Qiancheng Zhang; Jiankai Jiao (Metals)
In this study, the effect of high temperature on the mechanical performance of CoCrNi medium-entropy alloy octet-truss lattice material fabricated via laser powder bed fusion (LPBF) is investigated by compressive test and numerical simulation method. The results reveal that the strength and energy absorption performance of CoCrNi octet-truss lattice material with a hollow truss are higher than those of ones with a solid truss; however, they diminish by 30% and 50%, respectively, as temperature rises from 25 °C to 600 °C. As the temperature rises, the potential barrier for dislocation slip decreases, making it easier for dislocations to move at high temperatures and thus reducing the strength. CoCrNi octet-truss lattice materials present the failure mechanism of progressive collapse at varied temperatures. Meanwhile, the mechanical performance of the experimental testing agreed well with numerical simulation results. The numerical results show that the strength and energy absorption properties of the CoCrNi lattice materials increase as the relative density, however, decreases with increasing temperature. Additionally, CoCrNi octet-truss lattice materials maintain exceptional energy absorption performance at varied temperatures.